Albanian contexts of Kazimierz Mijal’s political activity in 1966–1978 (in documents from Central Committee of Albanian Party of Labour) - Czekalski, Tadeusz (Balcanica Posnaniensia. Acta et studia, 2025)
The article discusses the twelve-year period of political activity of Kazimierz Mijal, leader of the Communist Party of Poland, in Albania, where he stayed after fleeing Poland. In the plans of the Party of Labour of Albania leadership, Mijal's group was seen as a potential factor in destabilizing the political situation in Poland and, at the same time, strengthening the political position of Albanian communists in relation to China. The plans to use Mijal in Albanian political plans ended in failure and the party he led was incapable of effective actions. In 1978 he left Tirana for Beijing, where he continued his cooperation with the Communist Party of China.